(untitled) (International journal of artificial intelligence, 2025)
This article is devoted to the study of the pedagogical foundations of healthy lifestyle formation. The authors analyze the effective pedagogical methods and methods of its formation, taking into account not only the physical, but also the mental, social and spiritual aspects of a healthy lifestyle. The article emphasizes the importance of educating young people about a healthy lifestyle, educating them in areas such as physical activity, proper nutrition, hygiene and stress management. In pedagogical processes, the educational system, the role of teachers and parents are important for the formation of a healthy lifestyle. Also, the article focuses on the importance of educational institutions in the formation of a healthy lifestyle, the role of teaching students a healthy lifestyle through practical training, and new methods of pedagogical approaches.